2021
DOI: 10.1017/ice.2021.300
|View full text |Cite
|
Sign up to set email alerts
|

Intranasal octenidine for methicillin-resistant Staphylococcus aureus (MRSA) carriers and universal octenidine bathing reduced MRSA acquisition in an acute-care general ward

Abstract: In this quasi-experimental before-and-after study in a methicillin-resistant staphylococcus aureus (MRSA) high-prevalence acute-care dermatology ward from August 2016 to November 2018, patients admitted during intervention period who received additional topical intranasal octenidine were 63% less likely to acquire MRSA than those receiving universal daily octenidine bathing alone during baseline period (aOR, 0.37; 95% CI, 0.14–0.98).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 10 publications
0
6
0
Order By: Relevance
“…Against this background, OCT nasal gel could be an alternative for decolonizing S. aureus carriage in the nares. While several studies identified in this review used OCT nasal gel as a part of their interventions [19,20,22,24,28,30,41,46], we identified only one prospective study that directly compared the effectiveness of mupirocin, OCT, and chlorhexidine/neomycin nasal ointments for eradicating S. aureus [19]. This study clearly showed that OCT 0.1% was the least effective agent.…”
Section: Secondary Outcome Intranasal Oct Usementioning
confidence: 98%
See 3 more Smart Citations
“…Against this background, OCT nasal gel could be an alternative for decolonizing S. aureus carriage in the nares. While several studies identified in this review used OCT nasal gel as a part of their interventions [19,20,22,24,28,30,41,46], we identified only one prospective study that directly compared the effectiveness of mupirocin, OCT, and chlorhexidine/neomycin nasal ointments for eradicating S. aureus [19]. This study clearly showed that OCT 0.1% was the least effective agent.…”
Section: Secondary Outcome Intranasal Oct Usementioning
confidence: 98%
“…Of the remaining seven studies that compared the effects of OCT use to either other antiseptics or no antiseptic use, three evaluated the effects of nasal OCT (the results for this secondary outcome are summarized below) [19,20,22]. In the other four studies, one reported no reduction in nosocomial MRSA acquisitions (p = 0.31) and MRSA clinical infections (p = 0.96) in a setting where patients received OCT body washes pending the results of an MRSA admission screening (baseline phase).…”
Section: S Aureus Decolonization Infection Prevention and Nosocomial ...mentioning
confidence: 99%
See 2 more Smart Citations
“… 236 Also in Singapore, a study involving MRSA prevention in a high-prevalence acute-care dermatology ward, patients admitted during intervention period who received additional topical intranasal octenidine were 63% less likely to acquire MRSA than those receiving universal daily octenidine bathing alone during baseline period. 237 Denkel et al 238 performed a randomized controlled trial that compared CHG and octenidine with routine care on the prevention of central-line–associated bloodstream infections in 72 ICUs in Germany. Compared to routine bathing, neither showed significant preventive effect on CLABSI rates, although the authors stated that the study risked being underpowered; CLABSI rates in routine care group were lower than initially assumed.…”
Section: Implementing Active Surveillance Testing (Ast) Programsmentioning
confidence: 99%